Integrated proposition on tracking environment - Karunya, S; K. Kalaiselvi, Dr (International Journal of Engineering and Technology, 2018)
In current scenario, security level for an individual lies on a question mark.To overcome all situations based on safety. To provide a proper link to access things near us following header are used, they are GPS, GSM and GPRS. These systems help to track people on an individu-al basis which prevents the risk of kidnapping and other crimes happen to the people who depend on integrated proposition. This proposi-tion monitors the day to day happening of the user and provides the results to receiver of the person which consists of parents, guardian, local police station and others who access the integrated tracking, while they check the panic button.Â Â